Problematika Implementasi Pendekatan Saintifik dalam Pembelajaran Bahasa Arab di Madrasah Aliyah Hidayatul Mubtadiin Magetan - Ahmad Bashori (Study Program of Arabic Language Teaching, 2020)
The use of a scientific approach in learning Arabic aims to make students active, productive, critical, and analytical thinking in constructing concepts of knowledge and skills in Arabic. This study aims to describe the various problems faced by teachers and students in applying a scientific approach to learning Arabic in the Madrasah Aliyah Hidayatul Mubtadiin Magetan. The method used in this study is a qualitative method with a descriptive approach. Research data were obtained by interview, observation, and documentation. The data found were analyzed and interpreted using the Miles model, which is data reduction, data presentation, and concluding. The results of this study is that the problems of implementing a scientific approach to learning Arabic in the Madrasah Aliyah Hidayatul Mubtadiin Magetan relating to teachers are 1). Irrelevance of Arabic learning methods used by teachers with a philosophical scientific approach, and. 2) Lack of teacher initiative and innovation in encouraging students to be active, productive, think critically, and analytically in learning Arabic. The problems related to students are 1) The tendency of students to build their understanding of Arabic instantly, 2) Lack of encouragement in students to explore material that has been previously studied as a basis for contracting concepts in new material to be learned, and 3) Students' ignorance of the learning objectives being carried out. Mean while the problems related to teaching media are 1) The unpreparedness of teaching media used by teachers or students in supporting the learning process, and 2) Teacher and student inequality in empowering instructional media and those that are already available.